Debate as service learning - Othman, Moomala; Rajagopal, Darchaini; Abdul Rahman, Al Azmi; Pathil, Rabiathul Adawiah (IDOSI Publications, 2014)
Service learning (SL) is an innovative teaching methodology where students apply what they have learned in the classroom to serve a community. Through SL, students will combine learning, practice and reflection. This paper presents a service learning activity on a Debate Tournament undertaken by TESL undergraduates of UPM. In this project, there were three groups involved: 20 TESL teacher trainees, 200 lower form students aged 13-14 years old and lastly 40 upper form students aged 16 years old. In this program, the teacher trainees provided the service, teaching and coaching the lower forms about debate. The teacher trainers were the service provider while the form one and two students were the service recipients. The third group in this program were the form four students who assisted in running the debate competition. Through this program, the teacher trainees gained hands on experience teaching and managing students while the students had the opportunity to debate and improve their communicative as well as argumentative skills. During the program, observation of the teaching was undertaken by an evaluation team. A survey was undertaken to gauge the students’ satisfaction and their perception of the activity at the end of the activity. The trainee teachers wrote their experience in their reflection report followed by a content analysis of it. Later a descriptive analysis of the survey was carried out and the results showed both groups, teacher trainees and school students, benefited from the program.